Law/Culture: Power, Politics and the Political - Campbell, Elaine (2012)
Abstract: This paper is concerned with the dialectical relationship of law and culture. Recent academic work in the sociology of law positions such a relationship within a concept of power, specifically the power of law/culture to render the world meaningful not only in reciprocally constitutive ways but also in mutually deconstructive ways. While this kind of scholarship moves us some way beyond accounts which insist on law and culture as autonomous realms of human experience, it has created a context of consensus which is largely uncritical of their relationalities. Whilst not denying moments of creative synergy which emerge in productive and positive relations of mutuality, this discussion re-opens old antagonisms, and revisits law/culture as an ongoing contest and a dichotomous struggle over meaning, interpretation and judgement. I make use of a (familiar) Foucauldian vocabulary to delineate three modalities of power - sovereign, disciplinary and discursive – and use this as a framework for critically interrogating how law/culture stages different kinds of politics, which have varying effects in the broader political field of ‘justice'. The paper concludes by arguing for both a modified and an intensified approach to power which builds on the conceptual insights of an eclectic body of contemporary political theoretical work